The Effectiveness of Concept Sentence (CS) and Think Talk Write (TTW) Cooperative Learning Models in Writing Descriptive Text for Grade V Elementary School Students - Nila Ariana Ristianti; Sunardi Sunardi (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the differences and effectiveness results of using the Concept Centence and Think Talk Write cooperative learning models in order to develop descriptive text writing skills. The type of research used in this research is quasi-experimental or known as quasi-experimental research. Samples taken from elementary schools in Bancak District, Semarang Regency were SDN Jlumpang and SDN Pucung. The sampling technique in this research used a purposive sampling technique. The dependent variable in this research is descriptive text writing skills. The technique used in this research is using tests. Statistical analysis tests used for this research include normality tests, homogeneity tests with t-tests or mean difference tests. The results of this research are that there are differences in the Concept Centence and Think Talk Write learning models regarding descriptive text writing skills. The difference in the average pretest and posttest scores for experimental class 1 is 23,34. While for experimental class 2 it is 19,12. The t-test results show the value of Sig. (2-tailed) of 0,020 < 0,05, so that Concept Sentence learning has significantly superior effectiveness on the descriptive text writing skills of 5th students in Bancak District.